Developing practical module of Capita Selecta in mathematics assisted by android - Alpha Galih Adirakasiwi; Attin Warmi; Adi Ihsan Imami (Math Didactic: Jurnal Pendidikan Matematika, 2019)
In accordance with technological developments in the 21st century, the use of mathematical software can be used in the learning process. Teaching materials become one of the most important parts in the learning process in class. The teaching material developed in this study is a module. Decision modules are seen from expert assessors in their fields, then they are approved in a limited group and field trials conducted by researchers. This research develops an android assisted practicum module on selective capita. This research uses research and development methods. The design is the development using ADDIE. The stages of the ADDIE model design are: (1) analysis, (2) design, (3) development, (4) development, and (5) evaluation. The assessment instruments used consisted of expert material sheets, learning design experts, instructional media experts, limited trials and field tests as well as learning outcomes tests. Based on the results of this study produced a lab-assisted android module on a selective capita that meets the proper category to use.